2013
DOI: 10.1007/s10534-013-9640-4
|View full text |Cite|
|
Sign up to set email alerts
|

Conversion of a heme-based oxygen sensor to a heme oxygenase by hydrogen sulfide: effects of mutations in the heme distal side of a heme-based oxygen sensor phosphodiesterase (Ec DOS)

Abstract: The heme-based oxygen-sensor phosphodiesterase from Escherichia coli (Ec DOS), is composed of an N-terminal heme-bound oxygen sensing domain and a C-terminal catalytic domain. Oxygen (O2) binding to the heme Fe(II) complex in Ec DOS substantially enhances catalysis. Addition of hydrogen sulfide (H2S) to the heme Fe(III) complex in Ec DOS also remarkably stimulates catalysis in part due to the heme Fe(III)-SH and heme Fe(II)-O2 complexes formed by H2S. In this study, we examined the roles of the heme distal ami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 40 publications
0
8
0
1
Order By: Relevance
“…Moreover, as Table 1 shows, sulfheme was not detected in the HbI Gln/Val, Gln/Asn and Gln/Arg mutants, while the product was only observed in the Gln/His variant [14, 18]. Similarly, it was shown recently that the native Ec DOS-PAS heme sensor, which has Met and Arg in its distal site, does not form the sulfheme complex, supporting the role His in sulfheme formation [86]. Mutations of these residues by Ala, Ile, Leu and Glu did not induce formation of sulfheme, instead a verdoheme product was observed in the Arg/Ala and Arg/Ile mutants.…”
Section: Role Of His In Sulfheme Protein Formationmentioning
confidence: 69%
See 2 more Smart Citations
“…Moreover, as Table 1 shows, sulfheme was not detected in the HbI Gln/Val, Gln/Asn and Gln/Arg mutants, while the product was only observed in the Gln/His variant [14, 18]. Similarly, it was shown recently that the native Ec DOS-PAS heme sensor, which has Met and Arg in its distal site, does not form the sulfheme complex, supporting the role His in sulfheme formation [86]. Mutations of these residues by Ala, Ile, Leu and Glu did not induce formation of sulfheme, instead a verdoheme product was observed in the Arg/Ala and Arg/Ile mutants.…”
Section: Role Of His In Sulfheme Protein Formationmentioning
confidence: 69%
“…Verdoheme is a modified heme that has oxygen incorporated in the α-meso heme position. It is known for being one of the heme degradation steps in heme oxygenase [86]. Thus, it is evident that amino acids with: (i) non-polar aliphatic groups like glycine, alanine, valine and isoleucine, (ii) polar uncharged groups like glutamine and asparagine, (iii) aromatic group like phenylalanine and tyrosine, and (iv) positively charged groups like lysine and arginine, are not involved in the synthesis of the sulfheme species.…”
Section: Role Of His In Sulfheme Protein Formationmentioning
confidence: 99%
See 1 more Smart Citation
“…Accordingly, the autoxidation rates of mutants at the R97 residue are very fast [ 33 ]. Upon addition of H 2 S to the R97A and R97I mutants of Ec DOS-PAS-A-heme Fe(III), an O 2 -incorporated modified heme is formed with absorption band characteristic of verdoheme [ 40 ]. Time-dependent mass spectroscopic analyses confirmed that this treatment resulted in the formation of verdoheme and a trace of biliverdin, suggesting that H 2 O 2 or superoxide anion generated by these mutants would help to form verdoheme and biliverdin.…”
Section: Catalytic Activitiesmentioning
confidence: 99%
“…Our data confirm that the PAS fold can accommodate enzymatic activity, which suggests other PAS enzymes are likely to exist. Furthermore, it points to the fact that existing PAS domains can be evolved to catalyse reactions: engineered variants of a PAS oxygen sensor have been shown to display heme oxygenase activity [25]. N--dealkylation is a widespread reaction, catalysed by cytochromes P450 [12], FAD/quinone amine oxidases [26,27] and α--ketoglutarate--dependent Fe oxygenases [28].…”
mentioning
confidence: 99%